2016
DOI: 10.1007/s10973-015-5223-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of paracetamol-containing pastilles produced by melt technology

Abstract: The focus of this work was to apply melt technology for the formulation of a pastille containing paracetamol (PCT) in a solid dispersion with two sugar alcohols (xylitol and mannitol) and polyethylene glycol 6000 (PEG) as the carrier system components. Optimization of the pastillization was performed both statistically by using the Box-Behnken design and experimentally by determining the phase diagrams. For the latter and recrystallization of the components, differential scanning calorimetry detection was util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…The first scenario, where a drug is molecularly dispersed in the amorphous domains of PEG, wherein the recrystallization of a drug is usually observed after storing the dispersion at room temperature. The scenario is described for weak glasses like paracetamol (111), Telmisartan (112), and Celecoxib (113). The second scenario, where the polymer is in amorphous form, herein, it is established that PEG has the potential to vitrify after fusion and subsequent cooling.…”
Section: Poly Ethylene Glycol (Peg)mentioning
confidence: 99%
“…The first scenario, where a drug is molecularly dispersed in the amorphous domains of PEG, wherein the recrystallization of a drug is usually observed after storing the dispersion at room temperature. The scenario is described for weak glasses like paracetamol (111), Telmisartan (112), and Celecoxib (113). The second scenario, where the polymer is in amorphous form, herein, it is established that PEG has the potential to vitrify after fusion and subsequent cooling.…”
Section: Poly Ethylene Glycol (Peg)mentioning
confidence: 99%
“…It should be noted that recently the characterization of the investigated materials (e.g., crystallinity) using DSC as a semiquantitative conventional method has become common in scientific research [7][8][9]. It provides a possibility to predict the crystallinity of the examined materials, but to verify the accuracy of thermoanalytical measurements, the X-ray powder diffraction test is required [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of crystalline structure and the crystal lattice breaking force, less energy is needed for solubilization. Nevertheless, additional stabilization is needed for the preservation of the amorphous form from recrystallization [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…xylitol and sorbitol, as these are very similar molecules. In addition, our former studies (Katona et al, 2016) on similar pastilles containing no sorbitol revealed no such anomaly in the residuals (see the insert in Fig. 7C).…”
Section: Analysis Of Raman Spectra Of the Pastillesmentioning
confidence: 53%
“…In our previous studies we applied melt technology for the formulation of pastilles containing PCT (15.63%) as a model active agent, plus xylitol (61.25%), mannitol (15.31%) and polyethylene glycol 6000 (PEG 6000) (7.81%) as carriers (Katona et al, 2016). It was found that the components of the pastilles underwent recrystallization at different rates within the first 5 days after production, and phase separation, resulting in the appearance of a "shell" on the surface of the pastilles was detected.…”
Section: Discussionmentioning
confidence: 99%